Impact of institutional quality on economic performance of Eastern Africa: a panel data analysis - Fikadu Abera; Wondaferahu Mulugeta; Tesfaye Melaku (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
Nowadays, studies argued that international difference in prosperity across a country is the matter institutional quality. Thus, the poor economic performance of African’s is linked to their weak institutional quality. The aim of this study is to examine the extent to which institutional quality affect economic performance of 14 selected East African Countries; Burundi, Comoros, Djibouti, Ethiopia, Kenya, Madagascar, Malawi, Mozambique, Mauritius, Rwanda, Tanzania, Uganda, Zambia and Zimbabwe, over the period 2005-2016, using fixed effect and System GMM methods. The finding of this study confirms with the existing empirical study that economic institutions matter for economic performance among which control of corruption and government effectiveness has positive impact on economic performance, while rule of law has adverse impact. The finding of this study implies that that Eastern Africa with better institutions has a higher economic performance. Therefore, the Eastern Africa countries should improve those institutions that have positive impact, and promote and change those institutions that have adverse effect in way that it can promote economic development.